Artificial intelligence, data analytics and sports biomechanics: a new era or a false dawn? - Alderson, J.; Johnson, B. (ISBS Proceedings Archive (Michigan), 2018)
The adoption of wearable technologies combined with emerging and evolving data science techniques has the potential to do for sports biomechanists what the industrial revolution did for manufacturing. Yet the full capability of these technologies and methods will likely only be realised if sport scientists are embedded in their application and driving the questions being asked.